Актуальність проблеми розробки концепції відновлювального ремонту транспортної техніки - Лузан, Сергей Алексеевич (Eastern-European Journal of Enterprise Technologies, 2010)
On base of the analysis of the condition of the transport technician, residing in usages, is shown need of the concept development of the reconstruction repair of the details of the transport technician, taking into account type of the interfacing and way of the reconstruction to worn-out surface